Investigação dos possíveis efeitos do Round-up®, Glifosato e AMPA sobre linhagem de glioblastoma - Pereira, Bruna Ester Grumicker (2023)
Gliomas are tumors that originate in glial cells of the central nervous system (CNS). Among them, glioblastomas (GBM) stand out as a highly aggressive and lethal subtype, classified as grade IV by the World Health Organization (WHO) due to their high rate of progression. GBMs are characterized by rapid growth, invasive nature, and resistance to conventional treatments. Patients with GBM undergo surgical resection, chemotherapy, and radiotherapy as conventional treatment. The main chemotherapy drug used for treating these tumors is temozolomide (TMZ). However, these therapeutic strategies do not significantly improve prognosis or increase survival rates due to the low availability of chemotherapy to the CNS and the malignant characteristics of gliomas. These tumors often invade the surrounding brain tissue, making complete surgical removal difficult and increasing the likelihood of recurrence. Additionally, the blood-brain barrier presents a significant obstacle to the effective delivery of drugs, limiting the efficacy of systemic therapies. Due to these challenges, there is a crucial need for innovative therapies to effectively control the progression of GBMs. In this context, the main objective of this study was to investigate the action of Round-up®, Glyphosate, and AMPA on the U-251 GBM cell line to assess the antitumor action of these compounds. To achieve this, cell viability assays, assessment of the average inhibitory concentration, population doubling, and evaluation of lipid peroxidation level were conducted. As a result, significant cytotoxic effects were observed at different time points (24, 48, and 72 hours) and concentrations (1, 10, 25, 50, and 100 µg/mL) used, with the most pronounced outcome in Round-up® treatments for the MTT assays. Furthermore, IC50 values of 26.01 µg/mL for Round-up®, 1,636.15 µg/mL for Glyphosate, and 3,094.91 µg/mL for AMPA were obtained. Regarding the population doubling assay, abrupt cell mortality was observed at the beginning of treatments, especially with Round-up®, and in the long term, a trend of cell regeneration was noted. No significant results were found regarding the induction of oxidative stress by the evaluated compounds. Overall, the results indicated a greater cytotoxic effect when treating with Round-up® compared to Glyphosate and AMPA.